MENGENAL E-LEARNING SEBAGAI SALAH SATU BENTUK KEGIATAN PEMBELAJARAN - Husnul Khatimi (Universitas Lambung Mangkurat, 2006)
E-learning is very potential to make learning process more effective because student chance to have an interaction with lecturers, classmate, or lecture material is wider. Student can communicates with lecturer anytime by e-mail. Lecturer does. The communication can be closed one by one, or by public on billboard. The way of communication can be choiced, synchronus or asynchronus. With e-Learning, student can learns although he does not present at class physically. Learning process goes by interaction student and lecture materials that avaiable and can be accessed via internet. The flexibility of learning activity is happened by used of computer and internet technology. On this case, to join with e-learning, spesial software does not added for computer used. The main thing is connected to internet